Network Effects of the Productivity of Infrastructure in Developing Countries - Hurlin, Christophe (World Bank, Washington, DC, 2012)
Using panel data models, the author examines the threshold effects of the productivity of infrastructure investment in developing countries. He considers various specifications of an augmented production function that allow for endogenous thresholds. More precisely, these specifications are tested in a panel threshold regression model. The author's main robust result is the presence of strong threshold effects in the relationship between output and private and public inputs. Whatever the transition mechanism used, the testing procedures lead to strong rejection of the linearity of this relationship. In particular, the productivity of infrastructure investment generally exhibits some network effects. When the available stock of infrastructure is very low, investment in this sector has the same productivity as noninfrastructure investment. On the contrary, when a minimum network is available, the marginal productivity of infrastructure investment is generally largely greater than the productivity of other investment. Finally, when the main network is achieved, its marginal productivity becomes similar to the productivity of other investment.